In my opinion, this obscure lemma is the most beautiful part of the proof. It is surprisingly elegant.
Here is the lemma:
Lemma: Given that there exist p,q with the following properties:
(a) gcd(p,q)=1 (gcd = greatest common denominator)
(b) p,q have opposite parities (one is odd, one is even)
(c) p2 + 3q2 is a cube
Then there exists a,b such that:
(a) p = a3 - 9ab2
(b) q = 3a2b - 3b3
(c) gcd(a,b)=1
(d) a,b have opposite parities
Proof:
(1) Let u3 = p2 + 3q2. [Since we know that p2 + 3q2 is a cube.]
(2) We know that u is odd since p,q have opposite parities [that is, one is odd, one is even].
(3) We know then that u must be of the form a2 + 3b2. [Since any odd factor would also have to have the same form, see here for the lemma regarding odd factors of p2 + 3q2]
(4) Now, (a2 + 3b2)3 = (a2 + 3b2)[(a2 - 3b2)2 + 3(2ab)2]
since (a2 + 3b2)2 = a4 + 6a2b2 + 9b4 =
= a4 + 12a2b2 - 6a2b2 + 9b4 =
(a2 - 3b2)2 + 3(2ab)2
(5) And, (a2 + 3b2)[(a2 - 3b2)2 + 3(2ab)2] =
[ a(a2 - 3b2) - 3b(2ab)]2 + 3[a(2ab)+b(a2-3b2)]2 [See here for the proof.]
(6) And: [ a(a2 - 3b2) - 3b(2ab)]2 + 3[a(2ab)+b(a2-3b2)]2 =
= [a3 - 3ab2 - 6ab2]2 + 3(2a2b + a2b - 3b3)2 =
=[a3 -9ab2]2 + 3(3a2b - 3b3)2.
(7) Which combined with step (1) gives us:
p2 + 3q2 = [a3 -9ab2]2 + 3(3a2b - 3b3)2
(8) Which means that we could define a,b such that:
p = a3 -9ab2.
q = 3a2b - 3b3.
gcd(a,b)=1 [since otherwise, any common factor would divide p and q].
(9) We also know that a,b have opposite parities since:
(a) If a,b are both odd, then, p is even since p = odd - odd and q is even since q = odd - odd which is impossible since p,q have opposite parities.
(b) If a,b are both even, then p is even since p = even - even and q is even since q = even - even which is impossible.
QED